ANALISIS YURIDIS TERHADAP PERBEDAAN HARGA TRANSAKSI DENGAN HARGA YANG TERCANTUM DI DALAM AKTA PENGIKATAN JUAL BELI NOTARIS - SUNDARIA TAMBUNAN (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Syafruddin Kalo, SH, MHum2. Dr. Maria Kaban, SH, MHum3. Notaris Dr. Henry Sinaga, SH, MKn Buy and sell on land is the transfer of land right from a person to another one. It is common in a society since land is highly needed and has economic value. In the sale contract, object and price should be listed clearly. Price is very prominent in a sale contract so that if it is not listed it will change the meaning of the contract. Land is an object of sale-purchase contract which has economic value; therefore, every land right transfer will be subject to tax for the State. The seller is subject to PPh (Income Tax) and the buyer will be subject to BPHTB (Duty on Land and Building Right Acquisition). In calculating the tax of the land and building transfer, price has significant influence on the amount of its payment so that to increase the income of the State the tax is determined from the highest price. This makes land speculators not mention the real price in the deed to avoid a great number of taxes so that it is necessary to analyze the legal consequence of the price in a sale contract at taxation sector.